The Papanicolaou Society of Cytopathology Classification for Pulmonary Specimens : Application in Exfoliative Respiratory Cytology - Khari, Pooja; Srivastava, Sphruti; Mullick, Shalini (Annals of Pathology and Laboratory Medicine, 2020)
Background: Cytologic examination of specimens obtained from the respiratory tract is the primary and frequently used diagnostic technique in patients with respiratory symptoms or in those presenting with a pulmonary abnormality. Lung carcinoma is the leading cause of mortality in India. Hence, early diagnosis and effective treatment are keys to prolong the survival of lung cancer patients. Methods: 100 consecutive samples were taken which included 66 samples of bronchial wash, 27 samples of brush and 7 samples of bronchoalveolar lavage. These were viewed independently by two pathologists to study the ease of applicability, reproducibility and role of Papanicolaou Society of Cytopathology classification for pulmonary specimens. Result: The classification and terminology scheme recommend a six-tiered system comprising of non-diagnostic, negative, atypical, neoplastic (benign and neoplasms of low malignant potential), suspicious and positive for malignancy. In our study 43% were non-diagnostic, 33% were negative, 10% were atypical, 6% were suspicious for malignancy and 8% were malignant. Conclusion: This classification system of respiratory cytology is easy to apply and interpret with minimal inter-observer variation. Standardized classification and terminology system provide a framework for consistent inter-intra departmental and inter institutional communication of diagnostic, prognostic and management information needed for consistent and optimal patient care.